2011
DOI: 10.1002/term.466
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of human fibrin and fibrin-agarose oral mucosa substitutes generated by tissue engineering

Abstract: In regenerative medicine, the generation of biocompatible substitutes of tissues by in vitro tissue engineering must fulfil certain requirements. In the case of human oral mucosa, the rheological properties of tissues deserve special attention because of their influence in the acoustics and biomechanics of voice production. This work is devoted to the rheological characterization of substitutes of the connective tissue of the human oral mucosa. Two substitutes, composed of fibrin and fibrin-agarose, were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
3
24
0
1
Order By: Relevance
“…Nevertheless, potentiality for precise applications will depend on the biomechanical properties of the native tissue to be replaced, which should be matched by those of the artificial hydrogels. Previous works demonstrated that the values of the viscoelastic moduli of nanostructured and non‐nanostructured FA hydrogels at 0.1% of agarose are comparable to the ones of porcine cornea and human vocal fold mucosa, respectively . Our present study demonstrates that it is possible to adjust the biomechanical properties of fibrin and FA hydrogels within a broad range, by changing the agarose content and the hydration grade—the Young's Modulus ranges between 5 and 460 kPa, the compression elastic modulus between 1 and 75 kPa, G between 4 and 3100 Pa, G ′ between 15 and 4750 Pa and G ″ between 2 and 600 Pa.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Nevertheless, potentiality for precise applications will depend on the biomechanical properties of the native tissue to be replaced, which should be matched by those of the artificial hydrogels. Previous works demonstrated that the values of the viscoelastic moduli of nanostructured and non‐nanostructured FA hydrogels at 0.1% of agarose are comparable to the ones of porcine cornea and human vocal fold mucosa, respectively . Our present study demonstrates that it is possible to adjust the biomechanical properties of fibrin and FA hydrogels within a broad range, by changing the agarose content and the hydration grade—the Young's Modulus ranges between 5 and 460 kPa, the compression elastic modulus between 1 and 75 kPa, G between 4 and 3100 Pa, G ′ between 15 and 4750 Pa and G ″ between 2 and 600 Pa.…”
Section: Discussionsupporting
confidence: 63%
“…Previous works demonstrated that the values of the viscoelastic moduli of nanostructured and non-nanostructured FA hydrogels at 0.1% of agarose are comparable to the ones of porcine cornea and human vocal fold mucosa, respectively. 9,14 Our present study demonstrates that it is possible to adjust the biomechanical properties of fibrin and FA hydrogels within a broad range, by changing the agarose content and the hydration gradethe Young's Modulus ranges between 5 and 460 kPa, the compression elastic modulus between 1 and 75 kPa, G between 4 and 3100 Pa, G 0 between 15 and 4750 Pa and G 00 between 2 and 600 Pa. The adjustability of their biomechanical properties makes fibrin and FA hydrogels potential candidates for a good number of applications in tissue engineering ( Figs.…”
Section: Effect Of Agarose Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…In our work, we employed a fibrin-agarose scaffold that overcomes the drawbacks of both the animal-derived and the synthetic biomaterials used in other studies, such as the biocompatibility, biodegradability, fibroblastic infiltration capacity, morphologic and mechanical stability, and feasibility of an autologous source (17). Moreover, in comparison with other fibrin-based scaffolds previously reported (2,3,20), the fibrin-agarose improves the rheological stability while maintaining the viscoelastic properties of the native tissue (21). The construction of a human oral mucosa substitute intended for clinical application should ideally employ cells and biomaterials derived from the patient to avoid immunological concerns.…”
Section: Discussionmentioning
confidence: 99%